School-Aged Children With Higher Reflective Functioning Exhibit Lower Cardiovascular Reactivity - Borelli, Jessica L.; Ensink, Karin; Hong, Kajung; Sereno, Alexandra T.; Drury, Robert; Fonagy, Peter (Frontiers in Medicine, 2018)
Despite extensive theorizing regarding the regulatory role of reflective functioning (RF), few studies have explored the links between RF and physiological indices of emotion regulation, and none have examined these associations in children. Further, while scholars contend that RF promotes resilience via enhanced ability to process emotional experiences, including those occurring in attachment relationships, this argument has seldom been tested empirically in children. In the current study, we explore the association between RF and physiological measures of emotion reactivity and regulation, as well as the interaction of RF and attachment insecurity. We test these associations by examining children’s (N = 76; 8 to 12 years old) cardiovascular responses (respiratory sinus arrhythmia) to a standardized paradigm designed to evoke reactions regarding the experience and expression of attachment-related needs. Children also completed a semi-structured attachment interview, which was later coded for children’s attachment insecurity (operationalized as attachment dismissal and preoccupation) and RF. Our findings were largely consistent with theory and our hypotheses, suggesting that higher RF is associated with lesser cardiovascular reactivity (higher levels of RSA) during the stressor task and better recovery following the task. These links were especially strong for children with greater attachment preoccupation but did not vary as a function of children’s levels of attachment dismissal. These findings contribute to developmental theory in suggesting that RF is closely linked to physiological emotion regulation in children.